OECD glossary of statistical terms. (Organizational for Economic Co-operation and Development, 2008)
This glossary contains a comprehensive set of over 6,700 definitions of key terminology, concepts and commonly used acronyms derived from existing international statistical guidelines and recommendations. In the main, the definitions are quoted word for word from these sources and a detailed reference is provided to enable the user to refer to the complete source document to obtain further information where needed.--Publisher's description.